2001
DOI: 10.1046/j.1365-2141.2001.02542.x
|View full text |Cite
|
Sign up to set email alerts
|

The fleet feet of haematopoietic stem cells: rapid motility, interaction and proteopodia

Abstract: Summary. Haematopoietic stem cells (HSCs) have been extensively characterized regarding in vivo engraftment, surface epitopes and genetic regulation. However, little is known about the homing of these rare cells, and their intrinsic motility and membrane deformation capacity. We used high-speed optical-sectioning microscopy and inverted fluorescent videomicroscopy to study highly purified murine lineage-negative, rhodamine-low, Hoechst-low HSCs over time under various in vitro conditions. We discovered extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 29 publications
4
44
0
Order By: Relevance
“…The finding of rapid in vitro homing is concordant with the results of other in vitro adhesion studies 27 as well as with our own finding that 82% Ϯ 7% of lineage-negative, rhodamine-dull, Hoechst-dull (lin Ϫ rho low Ho low ) cells adhered to individual stromal cells within 1 hour of contact. 52 Further, other studies have shown that in vivo homing plateaus within the first few hours after transplantation 16,19 also agreeing with the results we present here.…”
Section: Discussionsupporting
confidence: 83%
“…The finding of rapid in vitro homing is concordant with the results of other in vitro adhesion studies 27 as well as with our own finding that 82% Ϯ 7% of lineage-negative, rhodamine-dull, Hoechst-dull (lin Ϫ rho low Ho low ) cells adhered to individual stromal cells within 1 hour of contact. 52 Further, other studies have shown that in vivo homing plateaus within the first few hours after transplantation 16,19 also agreeing with the results we present here.…”
Section: Discussionsupporting
confidence: 83%
“…They are highly motile, showing very rapid directed movement and rapid membrane deformation on cytokine exposure. 44 These cells also express a large number of stem cell-specific genes. Phillips et al 45 have reported on 2119 nonredundant gene products from fetal liver hematopoietic stem cells, using a subtracted cDNA library to generate a micro array chip.…”
Section: Stem Cell Genes and Functionsmentioning
confidence: 99%
“…Two different morphologies of pseudopodia have been reported (7). Magnupod extensions, described as thin, occurring at large distances (>300 μm) from the main cell body and showing rapid dynamic behavior, have been proposed by several groups to be equivalent to the structures known as cytonemes (29) or proteopodia (4,30). However, tenupodia correspond to those previously described as 'retraction fibers' (30,31).…”
Section: Discussionmentioning
confidence: 97%
“…A variety of actin-based cell surface membrane projections has been described in hematopoietic cells, including microvilli, lamellipodia, microspikes and filopodia (4). The Rho family of GTPases and the WASP family have been shown to be involved in the signal-transduction pathways that induce the formation of these projections.…”
Section: Introductionmentioning
confidence: 99%